Study of domestic wastewater (Greywater) in the district of Tamalanrea the city of Makassar - R. Ibrahim (Lowland Technology International, 2017)
Greywater problem is the environmental issues that have not received much attention from the public and the government. Greywater is one of the main sources of water pollution that needs to be managed properly. This study aimed to describe the characteristics and greywater management system that is understood and applied by communities in urban settlements through case Tamalanrea District of the Makassar city in Indonesia. The results can then be used as a basis in determining a solution for the management and treatment of greywater. Data were obtained from field observation and interview techniques using a questionnaire. Samples were collected from the outlet pipe greywater disposal of household and the combined channel in residential areas, and then analyzed in laboratory. The results showed that the parameters of pH, BOD, COD and TSS greywater of community settlements in the District Tamalanrea largely exceeded the threshold of environmental quality standards. While the greywater management system held separately from blackwater in a way to flow into the drainage channel without being processed first. The management conditions provide convenience in greywater treatment efforts so that it can be reused. In addition, it can reduce environmental pollution and increase the availability of groundwater.